2005
DOI: 10.1111/j.1365-2133.2005.06352.x
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale DNA microarray analysis of atopic skin lesions shows overexpression of an epidermal differentiation gene cluster in the alternative pathway and lack of protective gene expression in the cornified envelope

Abstract: Our results, showing downregulation of the cornified envelope genes and upregulation of the alternative keratinization pathway, are the first to suggest abnormal epidermal differentiation and defective defences as key abnormalities in AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
133
3
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(157 citation statements)
references
References 15 publications
18
133
3
3
Order By: Relevance
“…This is contradictory to previous studies by Sugiara et al [28] and Jensen et al [29]. Using gene microarrays, Sugiara et al [28] observed increased IVL and decreased LOR gene expression in lesional AD skin. Jensen et al [29] observed increased LOR and decreased IVL expression using immunohistochemistry and western blotting.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This is contradictory to previous studies by Sugiara et al [28] and Jensen et al [29]. Using gene microarrays, Sugiara et al [28] observed increased IVL and decreased LOR gene expression in lesional AD skin. Jensen et al [29] observed increased LOR and decreased IVL expression using immunohistochemistry and western blotting.…”
Section: Discussioncontrasting
confidence: 55%
“…This factor is not clearly defined in either of the previous studies [28,29]. AD lesions are bi-phasic with acute lesions having more of a Th2 cytokine milieu and chronic lesions having more of a Th1 cytokine milieu [19].…”
Section: Discussionmentioning
confidence: 69%
“…Recent data suggest that cutaneous expression of antimicrobial peptides/proteins may influence disease, and indeed altered defensin expression in lesional AD skin has been documented (30,31). Furthermore, AD has been linked to a region of chromosome 1 that contains numerous genes thought to encode antimicrobial proteins (32). At any point, the vast majority of skin-homing T cells are believed to be resident in the skin (33) and thus are likely to represent a diverse pool of cells with the potential TCR capacity to bind to SEB.…”
Section: Discussionmentioning
confidence: 99%
“…Impairment of epidermal-barrier function is a clinical hallmark of AD. Microarray analysis revealed decreased expression of FLG messenger ribonucleic acid (mRNA) in active atopic skin (Sugiura et al 2005). These findings suggest that dysfunction of FLG is an important factor in AD development.…”
Section: Discussionmentioning
confidence: 99%